Job Tasks, Computer Use, and the Decreasing Part-Time Pay Penalty for Women in the UK - Ahmed Elsayed; Andries de Grip; Didier Fouarge (Institute for the Study of Labor (IZA), 2014)
Using data from the UK Skills Surveys, we show that the part-time pay penalty for female workers within low- and medium-skilled occupations decreased significantly over the period 1997-2006. The convergence in computer use between part-time and full-time workers within these occupations explains a large share of the decrease in the part-time pay penalty. However, the lower part-time pay penalty is also related to lower wage returns to reading and writing which are performed more intensively by full-time workers. Conversely, the increasing returns to influencing has increased the part-time pay penalty despite the convergence in the influencing task input between part-time and full-time workers. The relative changes in the input and prices of computer use and job tasks together explain more than 50 percent of the decrease in the part-time pay penalty.
Keywords: J24; J31; 330; part-time work; pay penalty; job tasks; computer use